Peran Wanita Dalam Meningkatkan Kesejahteraan Keluarga Melalui Pemberdayaan UMKM - Tria silvia silvia; Rizka Putri Ramadani; Siti Kholijah; Sari Wulandari (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The participation of women clearly cannot be underestimated, the resilience of women in facing the crisis in 1998 is one of the concrete evidences recorded in the history of the nation's economy. In many developing countries, the movement of women from the agricultural sector to the industrial sector is faster than men. Bibliography research is research that is carried out by using a library in the form of books, memos, and information from previous research results. . On the other hand, the method used is story and analysis. This research results that in improving the economy and increasing the development of MSMEs in Indonesia, women have a very significant role in advancing MSMEs in Indonesia. In fact, there is a tendency for women to be more involved in home industry activities than in factory industrial activities. Keywords: Role of Women, Family Welfare, Increasing UMKM